Binding energy and biophysical properties of ionic liquid-DNA complex: understanding the role of hydrophobic interactions - Jumbri, Khairulazhar; Ahmad, Haslina; Abdul Malek, Emilia; Abdul Rahman, Mohd Basyaruddin (Elsevier BV, 2016)
The properties of DNA in ionic liquids (ILs) have been well studied. However, it is not widely known about the quantitative analysis of ILs such as the binding profile, which could offer a detailed insight of their binding characteristic. In this study, the binding energy of alkylimidazolium-based ILs ([Cnbim]Br where n = 2, 4 and 6) to calf thymus DNA was determined using fluorescence spectroscopy. It was found that the binding constant increased while the values of binding Gibbs energy decreased linearly with increase of alkyl chain length of the ILs. Based on these data, the contribution of each methylene group in the tail of ILs in IL-DNA complex was determined. Moreover, low quenching constant was observed from the competitive displacement of intercalation of ethidium bromide to DNA, hence confirming that ILs are not intercalator. The length of alkyl chain contributed to the increase in the thermal stability of DNA as observed from UV–visible spectra while the CD results indicated that DNA retained its B-form without significant change in the conformation of its base pairs. The findings show that although the stability of DNA is mainly due to the electrostatic attraction between cationic head charge group of imidazolium cation and the DNA phosphate groups, the contribution from the length of alkyl chains also plays a significant role in IL-DNA complex.